2019
DOI: 10.1016/j.yjmcc.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein inducer GGA*-59 reverses contractile and structural remodeling via restoration of the microtubule network in experimental Atrial Fibrillation

Abstract: Background: Atrial Fibrillation (AF) is the most common progressive tachyarrhythmia. AF progression is driven by abnormalities in electrical impulse formation and contractile function due to structural remodeling of cardiac tissue. Previous reports indicate that structural remodeling is rooted in derailment of protein homeostasis (proteostasis). Heat shock proteins (HSPs) play a critical role in facilitating proteostasis. Hence, the HSP-inducing compound geranylgeranylacetone (GGA) and its derivatives protect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…During stress or disease, such as AF, especially, activation of the heat shock transcription factor 1 regulates HSP transcription [ 17 ]. Within the HSP family, small HSPs, including HSP27, are probably the most important in maintaining proteostasis in cardiomyocytes by stabilizing the contractile proteins [ 18 , 19 , 20 , 21 ]. Previously, atrial HSP27 levels were found to be induced in atrial tissue samples of patients with paroxysmal AF, while tissue HSP27 levels get exhausted in patients with (longstanding) persistent AF [ 18 ], indicating that low tissue HSP levels are associated with AF progression.…”
Section: Introductionmentioning
confidence: 99%
“…During stress or disease, such as AF, especially, activation of the heat shock transcription factor 1 regulates HSP transcription [ 17 ]. Within the HSP family, small HSPs, including HSP27, are probably the most important in maintaining proteostasis in cardiomyocytes by stabilizing the contractile proteins [ 18 , 19 , 20 , 21 ]. Previously, atrial HSP27 levels were found to be induced in atrial tissue samples of patients with paroxysmal AF, while tissue HSP27 levels get exhausted in patients with (longstanding) persistent AF [ 18 ], indicating that low tissue HSP levels are associated with AF progression.…”
Section: Introductionmentioning
confidence: 99%
“…Various HSPs, including the HSP27 and HSP70, are involved in the protection against different forms of cellular stress by functioning as intra-cellular chaperones for other proteins [6,28]. In cardiomyocytes, HSP27 can bind to structural proteins and thereby shield them from damage and functional loss [6,9,10]. In accordance, upregulation of HSP27 in atrial tissue of dogs protected cardiomyocytes from AF-induced cellular stress and as such contributed to the maintenance of atrial tissue integrity and contractile function [6,28].…”
Section: Effect Of L-glutamine On Hsp and Metabolite Levelsmentioning
confidence: 97%
“…Emerging research findings indicate that heat shock proteins (HSP) mitigate AF onset and progression in experimental model systems for AF [6][7][8][9]. Especially HSP27 (small HSP) has shown promising protective effects against AF in-vitro [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sensitization results in opening and impairing mitochondrial metabolism through damage of complex I, while calpain inhibition decreases cardiac injury and improves heart function [77,78]. In addition, a recent study shows that post-treatment with the HSP-inducing compound geranylgeranyl acetone increases HSP-27 expression and enhances recovery from tachypacing-induced contractile dysfunction in cardiomyocytes [79]. Several studies have postulated an important role for CRF/CRF1 receptors in anxiety and in somatic, molecular and endocrine alterations evidenced during morphine withdrawal [80,81].…”
Section: Morphine Addiction and Hsp-27mentioning
confidence: 99%